Exploring Homoeopathic Interventions in Comorbid Presentation of IgA Nephropathy: A Case Report (Advancements in Homeopathic Research, 2025)
Introduction: IgA Nephropathy (IgAN) is the most  prevalent form ofglomerulonephritis  worldwide.  Disease progression may lead to advanced chronic  kidney disease (CKD) or end stage renal diseases  (ESRD). Clinically, IgAN can remain asymptomatic  or may present with persistent haematuria and  proteinuria. Definitive diagnosis requires renal  biopsy. Angiotensin-receptor blockers (ARBs) are  commonly used to slow disease progression;however  long-term use associated with potential adverse  effects. Case summary: This case report presents a  patient with symptoms including recurrent urinary  tract infections (UTIs) menstrual irregularity, foamy  and smoky coloured urine. Laboratory investigations  revealed with elevated serum creatinine levels,  and a renal biopsy confirmed a diagnosis of IgA  nephropathy (IgAN) Thuja occidentalis and Eel  serum were found effective in treatment of IgAN.  Patients outcomes were assessed using validated  tools including the impact outcome related to impact  on daily living (ORIDL) and measure yourself  medical outcome profile (MYMOP). To evaluate  the causal relationship between the intervention  and clinical outcomes the Modified Naranjo  Criteria for Homoeopathy (MONARCH) inventory  was employed. The findings suggest a potential  therapeutic benefit of homoeopathic remedies as  a part of integrative approach in the management  of IgAN, meriting further systematic investigation  through controlled clinical studies.
Keywords: Nephropathy; prevalent; glomerulonephritis; worldwide; Disease